Study of the spatial suitability of commercial pharmacies in Hail city using geographic information systems (GIS) - Alshurayhi, Asalah Maza (Journal of Humanities & Social Sciences, 2025)
This study aimed to identify the spatial distribution characteristics of commercial pharmacies in Hail City and examine their relationship with surrounding geographical and urban variables. The study adopted a descriptive-analytical approach and utilized Geographic Information Systems (GIS) for spatial analysis and to build a comprehensive database of pharmacy locations. The results revealed that the total number of commercial pharmacies in Hail reached 142 pharmacies by 2022, with a high concentration in the southern and central parts of the city, particularly in Al-Aziziyah and Al-Wusayta neighborhoods, while the northern and peripheral areas remain underserved. Most pharmacies are located along major commercial streets in a clustered distribution pattern, leaving large residential areas without adequate service, especially within new urban expansion zones. The study identified Al-Wusayta as the core focal point for pharmacy distribution, with the virtual center located in Al-Mahattah neighborhood. The analysis showed significant overlapping service areas in the city center due to high demand, while the coverage weakens toward the outskirts, such as in Mishar neighborhood. The study recommends setting clear planning criteria to regulate the spatial distribution of pharmacies, ensuring fair and balanced healthcare service provision for the city’s residents.